Evaluation of the Possible Impacts of New Residential Areas on Air Pollution in the Development Plan - Merve Arslan; Doğan Dursun (Doğal Afetler ve Çevre Dergisi)
In this study, the aim was to pre-determine the impact of urban planning decisions in emerging areas on air pollution. To achieve this, after conducting an air pollution analysis for the existing urban area of Erzurum (2021), a new air pollution analysis was produced for the target year 2027 in accordance with the proposed urban planning decisions within the study area. The goal was to determine how the changes in the urban fabric resulting from urban planning decisions would affect air quality. Weighted overlay analysis was used as the methodology in the study. The analysis was conducted based on four fundamental data groups: topographic data, which included elevation analysis: meteorological data, which included temperature analysis: air pollution data including PM10-SO2 analyses: and planning decision data, which included green areas, building height, population density, industrial areas and artificial surface analyses. Sub-criteria were established for each criterion, and an impact degree and weight score were determined for each sub-criterion. The analyses were conducted using the NetCAD and ArcGIS software. The study findings indicated that air pollution was more concentrated in areas with high building heights, population density, and a high percentage of artificial surfaces. Conversely, it was found that air pollution was less intense in areas with a greater amount of green space and a lower percentage of artificial surfaces. The analysis also indicated that the city’s temperature conditions and topographical structure had a negative impact on air pollution.